Analysis Of Polarity Conversion Of Npn To Pnp Proximity Sensor Using Switching Relay - Haris Gunawan; Rahmaniar; Ahmad Dani (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
Proximity sensors are essential components in industrial automation systems, particularly for non-contact object detection. NPN and PNP sensors differ in output polarity, which often creates compatibility issues when integrating them with control devices that require a specific type of input signal. A common problem occurs when an NPN proximity sensor must interface with a controller that only accepts PNP logic inputs, requiring a safe, stable, and practical method of polarity conversion. This study aims to analyze the conversion of output polarity from an NPN proximity sensor to a PNP configuration using a switching relay as the signal conversion component. The methodology includes designing the conversion circuit, conducting simulations, and performing direct testing of the relay’s switching response when receiving an output signal from the NPN sensor. The evaluated parameters include switching stability, response time, relay contact reliability, and compatibility with PLC or microcontroller inputs. The results indicate that the switching relay effectively performs polarity conversion, achieving a detection accuracy of more than 95%. The relay is capable of delivering a stable PNP logic output, although a slight delay occurs due to its mechanical switching operation. Additionally, the conversion circuit offers electrical isolation, making it safe and suitable for various industrial control systems. The study concludes that a switching relay provides a simple, economical, and compatible solution for converting NPN proximity sensor signals into PNP logic. Despite limitations in switching speed, this method remains highly applicable for low- to medium-speed automation processes. Further development is recommended using solid-state relays (SSR) or transistor-based drivers to improve switching speed and enhance system durability.